A methodological and clinical approach to measured energy expenditure in the critically ill pediatric patient - Silva-Gburek, Jaime; Zhu, Paola Hong; Mansour, Marwa; Walding, David; Coss-Bu, Jorge A. (Frontiers in Pediatrics, 2022)
The metabolic response to injury and stress is characterized initially by a decreased energy expenditure (Ebb phase) followed by an increased metabolic expenditure (Flow phase). Indirect calorimetry is a methodology utilized to measure energy expenditure and substrate utilization by measuring gas exchange in exhaled air and urinary nitrogen. The use of indirect calorimetry in critically ill patients requires precise equipment to obtain accurate measurements. The most recent guidelines suggested that measured energy expenditure by indirect calorimetry be used to determine energy requirements. This article reviews the methodological and clinical use of indirect calorimetry in critically ill pediatric patients.